Abstracts (Edited by Prof. Tahir Mahmood) - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2006)
Early changes in corneal sensation, ocular surface integrity, and tear-film function after laser-assisted subepithelial keratectomy Winter JH, Vidic B, Schwantzer G, Schmut O. J Cataract Refract Surg 2004; 30:2316-21 Effect of anterior capsule polishing on fibrotic capsule opacification: Three-year results Sacu S, Menapace R, Wirtitsch M, Buehl W, Rainer G, Findl O. J Cataract Refract Surg 2004; 30:2322-7. Predicting cataract surgery results using a macular function test Vryghem JC, Cleynenbreugel HV, Calster JV, Leroux K. J Cataract Refract Surg 2004; 30:2349-53. Incidence of and risk factors for residual posterior capsule opacification after cataract surgery Mootha VV, Tesser R, Quails C, J Cataract Refract Surg 2004; 30:2354-8.